Procedural fairness and equality of opportunity - Stefan T. Trautmann (Journal of Economic Surveys, 2022)
In this article, we discuss concepts of procedural fairness and equality of opportunity, and review the descriptive evidence regarding such procedural fairness preferences and their dynamic consistency. We then review the empirical relationship between equality of opportunity and preferences for redistribution. We discuss evidence derived from both survey and experimental studies.
Keywords: 330; equality of opportunity; outcome fairness; procedural fairness; redistribution